Nurses’ perceived role on transition of adolescents with intellectual disabilities - Grace R. Malapela; Gloria Thupayagale-Tshweneagae; Olabisi F. Ibitoye (African Journal of Disability, 2020)
Background: The nurses’ role on the transition of adolescents living with intellectual disabilities has always been neglected. Nurses’ primary role is promote health, provide nursing care, alleviate suffering, and to rehabilitate. Improving the quality of life for individuals with intellectual disabilities when they undergo the transition process from adolescence to adulthood was previously not considered a priority.